Designing a system for Online Orchestra: Microphone evaluation and cost-benefit analysis. Issue 2 (1st December 2017) - Geelhoed, Erik; Prior, David; Rofe, Michael
Online Orchestra is a telematic performance project that aimed to enable young and amateur musicians to make music online. Part of the aim of the project was to assess the extent to which specialist equipment is needed in order to enable a high-quality musical experience in a telematic environment. This article reports a microphone evaluation study in which untrained participants were asked to assess ten characteristics of quality in five samples, each recorded using different microphone configurations. Results show that participants rated DPA VO4099 clip-on microphones best, but that a stereo pair of Sure SM57s – which are over ten times cheaper – was rated a close second. Multidimensional scaling also shows that SM57s had the highest similarity to all other microphone configurations, suggesting they are a good alternative to costlier solutions.